Association between penicillin allergy labels and serious adverse events in hospitalized patients: a systematic review and meta-analysis - Shipeng Zhang; Shipeng Zhang; Tianyi Dong; Jiawen Xian; Jiawen Xian; Xinyue Xiao; Xinyue Xiao; Jiaqing Yuan; Jiaqing Yuan; Tong Zeng; Tong Zeng; Kuan Deng; et al. (Frontiers in Pharmacology)
BackgroundTo date, several studies have demonstrated that erroneous labeling of Penicillin allergy (PAL) can significantly impact treatment options and result in adverse clinical outcomes, while other studies have reported no negative effects. Therefore, to systematically evaluate these effects and investigate the association between adverse clinical outcomes and the Penicillin label, we conducted this meta-analysis.MethodSearches were conducted in the PubMed, Embase, Cochrane Library, and Web of Science databases from inception to 13 July 2024. The search strategy utilized terms (“antibiotic allergy label,” “penicillin allergy label,” and “allergy label”) and (“death,” “readmission,” “adverse outcome,” and “clinical adverse outcome”). In the study selection process, the PICOS framework and stringent inclusion/exclusion criteria were applied. The quality of the initially included studies was independently assessed using the Newcastle-Ottawa Scale (NOS). Data from the included studies, including relative risk (RR) and 95% confidence intervals (CI), were extracted and analyzed using Stata 16.0. Sensitivity analyses were conducted to validate the results. Heterogeneity was assessed using the I2 and Cochrane Q tests, and publication bias was evaluated using Egger’s test and funnel plot analysis.ResultsA total of 497 relevant studies were identified through four databases. Following a thorough screening process, 11 studies encompassing 1,200,785 participants were ultimately included. The combined evidence suggests that penicillin allergy labeling is associated with increased mortality RR = 1.06 (95% CI 1.06–1.07, I2 = 0.00%), acute heart failure (RR = 1.19, 95% CI 1.09–1.30, τ2 = 0.00, I2 = 92.39%), ICU events (RR = 1.10, 95% CI 1.01–1.19, τ2 = 0.00, I2 = 57.09%), and mechanical ventilation events (RR = 1.16, 95% CI 1.09–1.24, τ2 = 0.00, I2 = 23.11%). Additionally, there was no significant association with readmissions (RR = 1.05, 95% CI 0.95–1.16, I2 = 0.00%).ConclusionOur findings indicate that penicillin allergy labels are associated with an increased risk of mortality in patients, as well as being linked to acute heart failure, heightened ICU requirements, and mechanical ventilation.Systematic Review Registration:PROSPERO, identifier CRD42024571535. Available from: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD4202457153.